Impact of Trans-Boundary Pollution (PM-2.5) on the Air Quality of Dhaka City in Bangladesh - Dihan, Musfekur R; Nayeem, SM Abu; Choudhury, MAA Shoukat (Chemical Engineering Research Bulletin, 2021)
Clean air is a basic need of human beings for its existence. In recent years, air pollution in city areas, especially in Dhaka and Chittagong, has become a significant threat to health and well-being. Dhaka is found to suffer a high level of pollution during the dry season, which is from November to April, especially for Particulate Matter, PM2.5, concentration. From December to February this situation is found to be the worst crossing the WHO guidelines and National Ambient Air Quality Standard. Bangladesh is surrounded by countries with the fastest-growing economy like India and China who use coal-burning technologies for different purposes such as producing power and running mills. They release the lion’s share of the air pollutants in South Asia and these pollutants easily get transported to neighboring countries. This is known as transboundary pollution. This study investigates the contribution of transboundary transportation of PM-2.5 in the air quality of Dhaka city. Ninety-Six hours of air mass back trajectories were computed using the Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT-4) model and those trajectories were grouped into 6 clusters. Probability calculation showed that Dhaka city air has a higher probability of getting pollutants from long-range sources when air masses traveled through North, West, and North-West direction covering the North Eastern and North-Western territories of India, Nepal, and its neighboring areas. Concentration Weighted Trajectory (CWT) analysis also supported that those areas could be potential sources of getting unwanted PM-2.5 on our atmosphere. Chemical Engineering Research Bulletin 21(2020) 114-120